A note on collective action, cooperation, collusion, and voluntary production of public goods - Wiśniewski, Jakub Bożydar (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
In this note I challenge the claim that if it is possible to successfully produce public goods on a voluntary, decentralized basis, it must also be possible on the same basis to create stable cartels capable of reaping monopoly gains and frustrating consumer sovereignty. My proposed solution is rooted in the recognition that there is a fundamental asymmetry between the viability of beneficial and malevolent cooperation: the former is normally profitable both in the short and the long run, while the latter is profitable only in the short run
Keywords: collective action problem; public goods